Cytotoxin 1 from Naja atra Cantor venom induced necroptosis of leukemia cells. (July 2019) - Liu, Yamin; Ming, Wei; Wang, Yan; Liu, Sihong; Qiu, Yanfen; Xiang, Yongxin; Hu, Lili; Fan, Lingjie; Peng, Xiang; Wang, Han; Kong, Tianhan; Dong, Weihua; et al.
Abstract: Background: Cytotoxin 1 (CTX1) purified from Naja atra Cantor venom could inhibit cancer cell proliferation, but the mechanism is not clear. This study aimed to investigate the mechanism by which leukemia cells are killed by CTX1. Materials and methods: HL-60 and KG1a cells were treated with CTX1 and the cell death was detected. Results: The viability of HL-60 and KG1a cells decreased in a dose- and time-dependent manner after treatment with CTX1. CTX1 mainly induced late apoptosis and necrosis. The cell death induced by CTX1 could be rescued by specific necroptosis inhibitor Nec-1 but not by caspase inhibitor Z-VAD-fmk in HL-60 cells. In addition, CTX1 increased lysosome membrane permeability (LMP) and release of cathepsin B. Conclusion: CTX1 could induce necroptosis in leukemia cells, and it is related to LMP increase and cathepsin release. CTX1 could be a promising anti-cancer drug for leukemia therapy. Highlights: CTX1 mainly induced late apoptosis and necrosis in HL-60 and KG1a. CTX1 induced cell death could be rescued by necroptosis inhibitor Nec-1. CTX1 increased lysosome membrane permeability and release of cathepsin B.